PENGARUH PRICE PROMOTION DAN CONSUMER STREAMER INTERACTION TERHADAP IMPULSE BUYING MELALUI PERCEIVED RISK SEBAGAI VARIABEL MEDIASI PADA TIKTOK LIVE STREAMING - Syahputri, Riena Aprilia (Seminar Nasional Manajemen, 2025)
Ease of accessing the internet can be a reason for doing Impulse Buying. The purpose of this study is to determine the effect of Price Promotion and Consumer Streamer Interaction, Perceived Risk, and Impulse Buying. This study used the Purposive Sampling method using 200 respondents and using the Structural Equation Model (SEM) data analysis technique using the Partial Least Square (PLS) analysis method with Smart-PLS 3.0 software. The respondent criteria in this study were consumers who often make spontaneous purchases of food products through Tiktok Live Streaming. The results of this study indicate the influence of Price Promotion on Impulse Buying, Consumer Streamer Interaction on Impulse Buying, Price Promotion on Perceived Risk, Consumer Streamer Interaction on Perceived Risk, and Perceived Risk on Impulse Buying. In this study, it is hoped that UMKM can optimize their marketing strategies by frequently interacting with consumers through various media in addition to using the Live Streaming feature. Keywords : Price Promotion, Consumer Streamer Interaction, Perceived Risk, Impulse Buying, Live Streaming, Tiktok.